2019
DOI: 10.1109/access.2019.2935841
|View full text |Cite
|
Sign up to set email alerts
|

Study on Microstructural Evolution of Marble Under Cyclic Dynamic Impact Based on NMR

Abstract: In this paper, the evolution process of microstructures of fine-grained marble and coarse-grained marble under cyclic dynamic impact is studied. The split Hopkins pressure bars (SHPB) are used to apply multiple impacts on rock samples with a constant dynamic stress. And the microstructural changes caused by each impact were detected by a nuclear magnetic resonance (NMR) system. Porosity, transverse relaxation time (T 2) spectral distribution, pore size distribution and magnetic resonance imaging under differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Zhang [9] and Deng [10] discussed the micro-pore structure evolution of sandstone under freeze-thaw cycles by NMR analysis. Liu [11] and Jiang [12] carried out the cyclic freeze-thaw test and cyclic dynamic impact test on granite and sandstone, studying the microporosity changes of different rocks under cyclic impact by NMR. Li [13][14][15][16] carried out laboratory freeze-thaw cycle tests on sandstone materials at different cycle numbers and studied the pore structure evolution and fractal characteristics of pores with different radius under freeze-thaw cycles were studied by NMR and imaging analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang [9] and Deng [10] discussed the micro-pore structure evolution of sandstone under freeze-thaw cycles by NMR analysis. Liu [11] and Jiang [12] carried out the cyclic freeze-thaw test and cyclic dynamic impact test on granite and sandstone, studying the microporosity changes of different rocks under cyclic impact by NMR. Li [13][14][15][16] carried out laboratory freeze-thaw cycle tests on sandstone materials at different cycle numbers and studied the pore structure evolution and fractal characteristics of pores with different radius under freeze-thaw cycles were studied by NMR and imaging analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In the NMR test, the pore radius is proportional to the T2 value. Therefore, there is a T2 value that divides the pore fluid into bound fluid and free fluid, which is called the T2 cutoff value [31]. The T2 cutoff value divides the rock sample porosity into the bound fluid index (BVI) and free fluid index (FFI) by dividing the T2 spectrum distribution.…”
Section: T2 Spectralmentioning
confidence: 99%
“…Scholars have performed many experiments to determine the values of these model parameters. Based on previous studies, this paper assigns empirical values of 4, 2, and 10 to m, n, and C, respectively [31]. To directly reflect the characteristics of the pore connectivity with the freeze-thaw weathering cycles, the changes in porosity, IFP, MFP, T2 cutoff value, and permeability are plotted in Figures 8 and 9.…”
Section: T2 Spectralmentioning
confidence: 99%
See 1 more Smart Citation
“…elastic modulus and the shear modulus) under cyclic loading condition and found that rock specimens stiffen during loading and soften during unloading. Jiang et al [8] found that the porosity and pore size of marble rock gradually decrease under cyclic loading, which indicated that its framework becomes compacted. Apart from marble rock, red sandstone was also investigated by this research group, and the authors concluded that the damage variables showed a strong nonlinear relationship and increased with the loading cycles number [9].…”
Section: Introductionmentioning
confidence: 99%